Nancy Hurrell, The Egan Irish Harps: Tradition, Patrons and Players (2019) - Lawlor, Helen (Journal of the Society for Musicology in Ireland, 2020)
A review of Nancy Hurrell, The Egan Irish Harps: Tradition, Patrons and Players (Dublin: Four Courts Press, 2019). ISBN: 978-1-84682-759-4